THE IMPLEMENTATION OF PROJECT-BASED WORKSHEETS TO DEVELOP STUDENTS’ SCIENTIFIC PERFORMANCE THROUGH EDIBLE FILM PRODUCTION - Khoirunnisa, Kuntum Salsabilla; Sunarya, Risa Rahmawati; Sukmawardani, Yulia; Sari, Sari (KATALIS: Jurnal Penelitian Kimia dan Pendidikan Kimia, 2025)
The low scientific performance of students in learning chemistry is one of the main problems in education, mainly because the learning approach is still dominated by conventional methods and teacher-centered. Learning that does not actively involve students can hinder the development of critical thinking skills, problem solving, and students' scientific performance abilities. This study aims to develop students' scientific performance through the application of project-based worksheets in making edible film from jackfruit seed waste (Artocarpus heterophyllus). The research used a quantitative approach through the application of pre-experimental methods with a one-shot case study design involving 34 students of class XI majoring in Industrial Chemistry at one of the vocational high schools (SMK) in Cimahi City. The research instruments consisted of student activity observation sheets, project-based worksheets, and scientific performance assessment sheets. The results showed that student activity during learning obtained an average score of 97, worksheet work achieved an average score of 94, and student scientific performance of 92, each categorized as very good. These findings prove that the use of project-based worksheets can develop students' activeness, independence, and scientific abilities, and become an alternative solution to the problem of passive science learning in schools.